INNOVATION OF CORN SHEET (ZEA MAYS.L) AND AVOCADO SEEDS (PERSEA AMERICANA MILL) BISCUIT BASED ON ALTERNATIVE FOODS TO PREVENT STUNTING IN TODDLERS - Radooti Merlin Sagala; Saru Noliqo Rangkuti; Sefi Megawati; Azzahra Fernanda; Meta Safitri; Arini Aprilliani (RADJA PUBLIKA, 2025)
Stunting remains a critical issue in Indonesia due to chronic nutritional deficiencies. This study developed functional biscuits using corn silk and avocado seed flours in three ratios (25:75, 50:50, 75:25) to support toddler nutrition. Nutritional and sensory evaluations showed that the 50:50 formulation was optimal, containing 5.34% protein, 23.98% fat, and 68.01% carbohydrates. Although slightly below the SNI carbohydrate standard (≥70%), it met moisture and ash standards and was preferred in taste, color, and aroma. These findings highlight its potential as a supplementary food to help prevent stunting in early childhood.